Major Cause Of Women Divorce In India With Special Reference To Kashmir Valley - Muzamil Akther; Asifa munjkhal (Elementary Education Online, 2023)
The present study was an attempt to observe the impact of divorce Muslim Women and Kashmiri pundit women in Kashmir irrespective of their dwelling, work status and motherhood. The study shows that the majority of divorcee women are careless about themselves after divorce. Greater number of divorcee women is overburdened as a single parent. Most of the divorcee women’s children are rejected by father.